008 Is primary new daily persistent headache de novo chronic migraine and chronic tension-type headache?. Issue 9 (12th August 2022) - Cheema, Sanjay; Stubberud, Anker; Rantell, Khadija; Nachev, Parashkev; Tronvik, Erling; Matharu, Manjit
Abstract : Objective: To compare the clinical characteristics and treatment responses of primary new daily persis- tent headache (NDPH) to transformed chronic daily headache (T-CDH, encompassing chronic migraine and chronic tension-type headache). Methods: Analysis of prospectively collected clinical data in consecutive patients seen in a headache clinic between 2007 and 2019. Results: Inclusion criteria were met by 366 patients with NDPH and 696 with T-CDH. There was a lower female preponderance in NDPH than T-CDH (62.6% vs. 73.3%, p <0.001). Nausea, vomiting, photophobia, phonophobia, motion sensitivity, vertigo, and cranial autonomic symptoms were all less common in NDPH than T-CDH (all p<0.001). Most T-CDH patients (85%) met ICHD-3 criteria for chronic migraine, whereas fewer NDPH patients did (64%). Acute treatments were less effective in NDPH, and medication overuse was less common (16% vs. 42%, p<0.001). Response to most classes of oral preventive treatments was poor. The most effective treatment in NDPH was doselupin in 45.7% patients (95% CI 34.8-56.5%). OnabotulinumtoxinA was less likely to be effective in NDPH than T-CDH (34% vs. 49%, p=0.003). Conclusions: Whilst there is overlap in the phenotype and response to treatment of NDPH and T-CDH; NDPH appears to be less symptomatically diverse, and less responsive to treatment.